Propolis and its constituent caffeic acid suppress LPS-stimulated pro-inflammatory response by blocking NF-κB and MAPK activation in macrophages - Búfalo, Michelle Cristiane [UNESP]; Ferreira, Isabel; Costa, Gustavo; Francisco, Vera; Liberal, Joana; Cruz, Maria Teresa; Lopes, Maria Celeste; Batista, Maria Teresa; Sforcin, José Maurício [UNESP] (Elsevier, 2013)
Ethnopharmacological relevance Propolis is a bee product with numerous biological and pharmacological properties, such as immunomodulatory and anti-inflammatory activities. It has been used in folk medicine as a healthy drink and in food to improve health and prevent inflammatory diseases. However, little is known about its mechanism of action. Thus, the goal of this study was to verify the antioxidant activity and to explore the anti-inflammatory properties of propolis by addressing its intracellular mechanism of action. Caffeic acid was investigated as a possible compound responsible for propolis action. Materials and methods The antioxidant properties of propolis and caffeic acid were evaluated by using the 2,2-Diphenyl-1-picrylhydrazyl free radical (DPPH) scavenging method. To analyze the anti-inflammatory activity, Raw 264.7 macrophages were treated with different concentrations of propolis or caffeic acid, and nitric oxide (NO) production, a strong pro-inflammatory mediator, was evaluated by the Griess reaction. The concentrations of propolis and caffeic acid that inhibited NO production were evaluated on intracellular signaling pathways triggered during inflammation, namely p38 mitogen-activated protein kinase (MAPK), c-jun NH2-terminal kinase (JNK1/2), the transcription nuclear factor (NF)-κB and extracellular signal-regulated kinase (ERK1/2), through Western blot using specific antibodies. A possible effect of propolis on the cytotoxicity of hepatocytes was also evaluated, since this product can be used in human diets. Results Caffeic acid showed a higher antioxidant activity than propolis extract. Propolis and caffeic acid inhibited NO production in macrophages, at concentrations without cytotoxicity. Furthermore, both propolis and caffeic acid suppressed LPS-induced signaling pathways, namely p38 MAPK, JNK1/2 and NF-κB. ERK1/2 was not affected by propolis extract and caffeic acid. In addition, propolis and caffeic acid did not induce hepatotoxicity at concentrations with strong anti-inflammatory potential. Conclusions Propolis exerted an antioxidant and anti-inflammatory action and caffeic acid may be involved in its inhibitory effects on NO production and intracellular signaling cascades, suggesting its use as a natural source of safe anti-inflammatory drugs. © 2013 Elsevier B.V.
Keywords: Anti-inflammatory action; Caffeic acid; Mitogen-activated protein kinases; Nitric oxide; Nuclear factor-κB; Propolis; caffeic acid; immunoglobulin enhancer binding protein; mitogen activated protein kinase; mitogen activated protein kinase 1; mitogen activated protein kinase p38; nitric oxide; propolis; protein c jun; antiinflammatory activity; antioxidant activity; drug cytotoxicity; enzyme activation; human; human cell; in vitro study; intracellular signaling; liver cell; liver cell carcinoma; liver toxicity; macrophage; Western blotting; Apoidea